CARDIAC COMPLICATIONS IN DUCHENNE MUSCULAR DYSTROPHY IN CHILDREN - Ioana Grigore; Mariana Frasin; Georgeta Diaconu (Romanian Journal of Pediatrics, 2015)
Cardiac complications are frequently diagnosed in Duchenne muscular dystrophy (DMD), clinical manifestations generally appear after age 10. ECG recordings objectified various changes in these patients, the most common being represented by extensive R waves in V1, left deep Q waves, conduction abnormalities and arrhythmias. Echocardiographic examination may objective the presence of subclinical cardiac dysfunction in children under 12 years old diagnosed with DMD. In patients where standard echocardiographic examination is normal, myocardial performance index is a parameter useful in early detection of asymptomatic cardiac abnormalities. Cardiovascular magnetic resonance provides information both on left ventricular systolic function and myocardial tissue changes and occurrence of fibrosis, lesions rarely objectified before the age of 10 years. All these explorations should be considered in children with DMD at the end of a complete neurological exam.